PENGARUH DUAL TASK EXERCISE DALAM MENINGKATKAN KESEIMBANGAN DAN KEMAMPUAN FUNGSIONAL PADA PASIEN OSTEOARTHRITIS LUTUT DERAJAT DUA - Kharismawan, Putu Mulya; Daryono; Larashati, Ni Putu Dwi (Jurnal Kesehatan Terpadu, 2025)
Knee osteoarthritis is a degenerative condition that affects balance and functional mobility of the knee joint. The application of dual-task exercise using a Bola bosu is expected to improve these impairments. Objective: To evaluate the effectiveness of dual-task exercise in improving balance and functional ability in patients with grade II knee osteoarthritis. Methods: This study employed a pre-experimental design with a one-group pretest-posttest approach. A total of 15 participants were selected using a consecutive sampling technique. Balance was measured using the Berg Balance Scale, while functional ability was assessed using the Timed Up and Go (TUG) test and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire. Results: The paired t-test showed a significant improvement in balance (p = 0.001) and functional ability (p = 0.001). Conclusion: Dual-task exercise effectively improves balance and functional ability in patients with grade II knee osteoarthritis. Implications: Dual-task exercise can be considered a therapeutic option for rehabilitation programs in patients with grade II knee osteoarthritis.